The Effect of Professional Skepticism, Locus of Control and Independence on Auditors' Ability to Detect Fraud (Case Study at Bank ABC) - Andrianus Pujianto; Yulis Diana Alfia (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This research aims to analyze the influence of professional skepticism, locus of control and independence on the auditor's ability to detect conditions. This research uses quantitative methods. Data was collected using questionnaire techniques. The respondents in this study were 40 people consisting of internal auditors at Bank ABC in Jakarta City. Three hypotheses were formulated and tested using regression analysis. The research results show that professional skepticism and independence have a significant effect on the auditor's ability to detect situations. Meanwhile, locus of control has no effect on the auditor's ability to detect fraud.